Floral Induction in Arabidopsis by FLOWERING LOCUS T Requires Direct Repression of BLADE-ON-PETIOLE Genes by the Homeodomain Protein PENNYWISE . Issue 3 (28th September 2015) - Andrés, Fernando; Romera-Branchat, Maida; Martínez-Gallegos, Rafael; Patel, Vipul; Schneeberger, Korbinian; Jang, Seonghoe; Altmüller, Janine; Nürnberg, Peter; Coupland, George
Abstract : Direct repression of lateral organ boundary genes in the shoot meristem is required for flowering induction. Abstract: Flowers form on the flanks of the shoot apical meristem (SAM ) in response to environmental and endogenous cues. In Arabidopsis ( Arabidopsis thaliana ), the photoperiodic pathway acts through FLOWERING LOCUS T ( FT ) to promote floral induction in response to day length. A complex between FT and the basic leucine-zipper transcription factor FD is proposed to form in the SAM, leading to activation of APETALA1 and LEAFY and thereby promoting floral meristem identity. We identified mutations that suppress FT function and recovered a new allele of the homeodomain transcription factor PENNYWISE (PNY). Genetic and molecular analyses showed that ectopic expression of BLADE-ON-PETIOLE1 ( BOP1 ) and BOP2, which encode transcriptional coactivators, in the SAM during vegetative development, confers the late flowering of pny mutants. In wild-type plants, BOP1 and BOP2 are expressed in lateral organs close to boundaries of the SAM, whereas in pny mutants, their expression occurs in the SAM . This ectopic expression lowers FD mRNA levels, reducing responsiveness to FT and impairing activation of APETALA1 and LEAFY . We show that PNY binds to the promoters of BOP1 and BOP2, repressing their transcription. These results demonstrate a direct role for PNY in defining the spatial expression patterns of boundary genes and the significance of this process for floral induction by FT.